Compassionate mindful inquiry in therapeutic practice : a guide for mindfulness teachers, yoga teachers and complementary medicine practitioners /: a guide for mindfulness teachers, yoga teachers and complementary medicine practitioners. (2020) - Atkinson, Karen
No abstract available